Activity Dependence of a Novel Lectin Family on Structure and Carbohydrate-Binding Properties - Chikalovets, Irina; Filshtein, Alina; Molchanova, Valentina; Mizgina, Tatyana; Lukyanov, Pavel; Nedashkovskaya, Olga; Hua, Kuo-Feng; Chernikov, Oleg (Molecules (Basel, Switzerland), 2019)
A GalNAc/Gal-specific lectins named CGL and MTL were isolated and characterized from the edible mussels Crenomytilus grayanus and Mytilus trossulus. Amino acid sequence analysis of these lectins showed that they, together with another lectin MytiLec-1, formed a novel lectin family, adopting β-trefoil fold. In this mini review we discuss the structure, oligomerization, and carbohydrate-binding properties of a novel lectin family. We describe also the antibacterial, antifungal, and antiproliferative activities of these lectins and report about dependence of activities on molecular properties. Summarizing, CGL, MTL, and MytiLec-1 could be involved in the immunity in mollusks and may become a basis for the elaboration of new diagnostic tools or treatments for a variety of cancers.